The story of the youth club - Lindström, Lisbeth (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2012)
As a case study, young people visiting youth clubs and similar meeting places in a local council in northern Sweden, was explored in terms of place, space and activities of the club or meeting places and discussed in the perspective of social and cultural transformation. To collect data over a 6-month period, several visits were carried out to the youth clubs and similar meeting places. During the visits, notes and photographs were taken of the physical environment of the clubs. As a theoretical framework, theories of citizenship were used. The following questions are of special interest: where are these meeting places located; what kind of visitors do they attract; what kind of activities do they offer; how do visitors use the space and what kind of citizenship do they support? The results of the study show first that these places are more attractive to boys than to girls. Second, youth clubs and similar meeting places offer many activities for both boys and girls, which are used in a traditional female or male context. Third, those who visit youth clubs and similar meeting places at their leisure time are offered the opportunity of taking an active role in their transition to citizenship. Validerad; 2012; 20120313 (lisl)